Research on tourism demand forecast based on BP neural network -- Taking the number of tourists in Mulan Scenic spot in Huangpi District for example - Yin, Na; Sutunyarak, Chonlavit (Edelweiss Applied Science and Technology, 2024)
With the development of the economy and society, the public's demand for tourism is getting higher and higher, followed by the environmental carrying capacity of the destination, the bearing capacity of traffic reception facilities, and the psychological carrying capacity of tourism residents being affected by different degrees. This paper took the analysis of the number of tourists in Mulan Scenic Spot in Huangpi District for the May Day holiday as an example, combined with the BP neural network algorithm, forecast the tourism demand, and put forward the local government's suggestions on holiday tourism management based on the data research.